A single amino acid substitution in human APOBEC3G antiretroviral enzyme confers resistance to HIV-1 virion infectivity factor-induced depletion - Xu, Hongzhan (National Academy of Sciences, 2004)
HIV-1 and other retroviruses occasionally undergo hypermutation, characterized by a high rate of G-to-A substitution. Recently, the human apolipoprotein B mRNA-editing, enzyme-catalytic, polypeptide-like 3G (APOBEC3G), first identified as CEM15, was shown to be packaged into retroviral virions and to deaminate deoxycytidine to deoxyuridine in newly synthesized viral minus-strand DNA, thereby inducing G-to-A hypermutation. This innate mechanism of resistance to retroviral infection is counteracted by the HIV-1 viral infectivity factor (Vif), which protects the virus by preventing the incorporation of APOBEC3G into virions by rapidly inducing its ubiquitination and proteasomal degradation. To gain insights into the mechanism by which Vif protects HIV-1 from APOBEC3G, we substituted several amino acids in human APOBEC3G with equivalent residues in simian APOBEC3Gs that are resistant to HIV-1 Vif and determined the effects of the mutations on HIV-1 replication in the presence and absence of Vif. We found that a single amino acid substitution mutant of human APOBEC3G (D128K) can interact with HIV-1 Vif but is not depleted from cells; thus, it inhibits HIV-1 replication in an HIV-1 Vif-resistant manner. Interestingly, rhesus macaque simian immunodeficiency virus 239 or HIV-2 Vif coexpression depleted the intracellular steady state levels of the D128K mutant and abrogated its antiviral activity, indicating that it can be a substrate for the proteasomal pathway. The HIV-1 Vif-resistant mutant APOBEC3G could provide a gene therapy approach to combat HIV-1 infection.